A case of neuroendocrine carcinoma in the hepatic hilar lymph nodes concomitant with an adenocarcinoma of the gallbladder. Issue 1 (December 2016) - Okada, Haruka; Uchida, Yoichiro; Matsuzaki, Naomi; Goto, Toru; Nishimura, Satoshi; Kurita, Akira; Nishimura, Takafumi; Yazumi, Shujiro; Terajima, Hiroaki
Abstract Background Neuroendocrine tumors (NETs) are rare especially in the gallbladder. They have not been elucidated in the pathogenesis, clinicopathological characteristics, and treatment options. Case presentation We present a 76-year-old woman with a gallbladder tumor and hepatic hilar lymph node swelling. The lymph node biopsy demonstrated neuroendocrine carcinoma (NEC). We performed cholecystectomy, hepatic hilar lymphadenectomy, extrahepatic biliary duct resection, and hepaticojejunostomy prior to chemotherapy. Pathological examination revealed the gallbladder mass was an adenocarcinoma invading to the muscular layer without any NEC components, whereas the hepatic hilar lymph nodes were filled with high-grade NEC cells with negligible area of adenocarcinoma. The patient received general chemotherapy consisting of carboplatin and etoposide, but a recurrence in the para-aortic lymph nodes occurred 4 months after surgery. Conclusions We report a rare case of NEC of the hepatic hilar lymph nodes that were concomitant with an adenocarcinoma of the gallbladder. High-grade NEC generally has an aggressive behavior and an optimal treatment strategy should be chosen for each patient.